Self-Actualization of the Main Character in Perahu Kertas and Madre by Dee (A Humanistic Psychology Study) - Sanga, Mega; Latupapua, Falantino Eryk; Latupeirissa, Elsa (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The novels Perahu Kertas and Madre are compelling for discussion since they illustrate the self-actualization journeys of two young individuals, Keenan and Tansen, in distinct narratives. Both individuals realize their identities through their pursuits as a painter and a bread entrepreneur, respectively. This work aims to elucidate the actualization of Keenan in the novel Perahu Kertas and Tansen in the novel Madre. The employed research methodology is descriptive qualitative, utilizing a humanistic psychology framework. The realization of Keenan's utmost achievement was demonstrated by his diligence and determination. His audacity to undertake seemingly irrational decisions in pursuit of painting defined his identity. Similar to Keenan, Tansen's self-actualization is propelled by the support of his peers, which inspires him to pursue self-actualization through diligent effort. Tansen has fully realized self-actualization, demonstrated by his endeavors to rejuvenate the practically obsolete Tan de Bakker bakery and transform it into a renowned establishment, despite his initial reluctance to perpetuate his grandfather's enterprise.